The influence of extraction methods on composition and antioxidant properties of rice bran oil - Noppawat Pengkumsri (2018)
© 2015, Sociedade Brasileira de Ciencia e Tecnologia de Alimentos, SBCTA. All rights reserved. The current study was employed to assess the influence of the different extraction methods on total tocols, γ-oryzanol content, and antioxidant properties of Chiang Mai Black rice, Mali Red rice, and Suphanburi-1 Brown rice bran oil. Rice bran oil (RBO) was extracted by Hexane, Hot pressed, Cold pressed, and Supercritical Fluid Extraction (SFe) methods. High yield of RBO was extracted by hexane and SFe methods. Total and subgroups of tocols, and γ-oryzanol content were determined by HPLC. The hexane extracted sample accounts for high content of γ-oryzanol and tocols. Besides, all of RBO extracts contain a significantly high amount of γ-tocotrienol. In vitro antioxidant assay results indicated that superior quality of oil was recovered by hexane extraction. The temperature in the extraction process also affects the value of the oil. Superior quality of oil was recovered by hexane extraction, in terms of phytochemical contents and antioxidant properties compared to other tested extraction methods. Further, thorough study of factors compromising the quality and quantity of RBO recovery is required for the development of enhanced functional foods and other related products.